Gambaran Ureum dan Kreatinin pada Pasien Penyakit Ginjal Kronik yang Menjalani Hemodialisis - Roni Roni Afriansya; Eko Naning Sofyanita; Suwarsi Suwarsi (Poltekkes Kemenkes Semarang, 2020)
Chronic Kidney Disease is evident if the blood urea level is more than 200 mg/dl. Uremia causes a malfunction in almost all organ systems such as; fluid and electrolyte disorders, metabolic endocrine, neuromuscular, cardiovascular and pulmonary, skin, gastrointestinal, hematological, and immunological. Hemodialysis is an attempt to reduce the symptoms of uremia so that the patient's clinical condition can also improve. The purpose of this study was to determine the description of Ureum and Creatinine in CKD Patients undergoing Hemodialysis. This type of research is observational descriptive. The sample included all CKD patients undergoing hemodialysis at the Ir Sukarno Sukoharjo Regional Hospital in 2019 who met the inclusion criteria, so as many as 83 samples were obtained. The type of data is secondary data obtained from medical records. The results showed that most patients were in the 40-60 years age group of 72% and the majority of the male sex were 51 patients (61%). Urea and creatinine appearance in patients undergoing hemodialysis has increased very high. In 83 patients with CKD increased serum creatinine levels ( 100%) with a mean creatinine level in men of 11.80 mg / dL and women of 9.73 mg / dL and an increase in ureum levels with a mean of 167 men, 09 mg / dL and women of 164.39 mg / dL. This study concludes that all patients with CKD have increased levels of urea and creatinine by more than 100%.